Entre experiências e diferenças nas mídias digitais : modos de uso e desejos-hashtag na #seráqueéracismo - Baboni, Renata (Universidade Federal de São Carlos, 2016)
The research inquired into the relation among ways of using and the identification processes involving #seráqueéracismo on Twitter. Therefore, it unveiled how the differences were articulated in the discourses about racialized experiences by means of analyzing published content and semi-structured interviews with the influencers, widely shared narratives producers. Analytical axes such as experiences and diferences were used, in the relation between gender, sexuality, race and social class, through Queer Studies. In these negotiations about differences, the hashtag, communication mode about itself, was very characterized by narratives about emotions. These ways of using it, on one hand, are configured by a certain contestatory practice of a racist current norm's perception in some narratives and, on the other hand, enabled an aperture of a discussion about the existence or not of racism in other narratives. In this game of experiences ambivalences, sometimes were reproduced and sometimes were contested normalizations about differences, by means of position delimitations and stereotyping individuals. It was also very frequent the description of racism in the other, directly linked to the social acknowledge desire that rules those ways of using (so many times denied to the nonwhite, conferring on them the victimization and accountability on the existence of racism).
Between experiences and differences in digital media : ways of using and desires-hashtag on #seráqueéracismo
Keywords: Mídias Digitais; #Seráqueéracismo; Hashtag; Estudos de Gênero; Sociologia das diferenças; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS